Persistent Hepatitis E virus infection across England and Wales 2009‐2017: Demography, virology and outcomes. Issue 2 (2nd November 2020) - Ankcorn, Michael; Said, Bengü; Morgan, Dilys; Elsharkawy, Ahmed M; Maggs, James; Ryder, Stephen; Valliani, Talal; Gordon, Fiona; Abeysekera, Kushala; Suri, Deepak; McPherson, Stuart; Galliford, Jack; et al.
Abstract: The first clinical case of persistent HEV infection in England was reported in 2009. We describe the demography, virology and outcomes of patients identified with persistent HEV infection in England and Wales between 2009 and 2017. A series of 94 patients with persistent HEV infection, defined by HEV viraemia of more than 12 weeks, was identified through routine reference laboratory testing. Virology, serology and clinical data were recorded through an approved PHE Enhanced Surveillance System. Sixty‐six cases (70.2%) were transplant recipients, 16 (17.0%) had an underlying haematological malignancy without stem cell transplantation, six (6.4%) had advanced HIV infection, five (5.3%) were otherwise immunosuppressed, and one patient (1.1%) had no identified immunosuppression. Retrospective analysis of 46 patients demonstrated a median 38 weeks of viraemia before diagnostic HEV testing. At initial diagnosis, 16 patients (17.0%) had no detectable anti‐HEV serological response. Of 65 patients treated with ribavirin monotherapy, 11 (16.9%) suffered virological relapse despite undetectable RNA in plasma or stool at treatment cessation. Persistent HEV infection remains a rare diagnosis, but we demonstrate that a broad range of immunocompromised patients are susceptible. Both lack of awareness and the pauci‐symptomatic nature of persistent HEV infection likely contribute to significant delays in diagnosis. Diagnosis should rely on molecular testing since anti‐HEV serology is insufficient to exclude persistent HEV infection. Finally, despite treatment with ribavirin, relapses occur even after cessation of detectable faecal shedding of HEV RNA, further emphasising the requirement to demonstrate sustained virological responses to treatment.